Antibacterial Activity of Acylated Flavonol Glycoside from Waltheria indica - Maheswara, M.; Koteswara Rao, Y.; Madhava Rao, V.; Rao, C.Venkata (Asian Journal of Chemistry, 2010)
A rare acylated flavonol glycoside, kaempferol 3-O-β-D-(6''-E-p-coumaryl)-glucopyranoside (1), together with five known flavonoids, quercetin 3-O-glucopyaranoside (2), kaempferol-3- O-α-L- rhamnoside (3), kaempferol-3-O-β-D-glucopyranoside (4), quercetin (5) and kaempferol (6) were isolated from the whole plant of Waltheria indica. The structures of these compounds were elucidated by FABMS, UV, 1D and 2D NMR spectroscopy including COSY, HSQC and HMBC experiments and acid hydrolytic and saponification studies. Compound 1 was isolated for the first time from the family Sterculiaceae. These compounds were screened for antibacterial activity against Staphylococcus aureus and Escherichia coli.